Effective Microorganisms Improve Nutrient Use Efficiency, Growth, and Yield of Inthanon Melon under Drip Hydroponic - Ade Hilman Juhaeni; Yanto Yulianto; Leny Yuliyani; Alin Robiah Al Adawiah; Aslikh Lana Dina; Yudhi Arie Priyanto; Ikhsan Rafli Muharam (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Hydroponic cultivation of melon (Cucumis melo L.) Inthanon variety is a high-income potential product, especially in Tasikmalaya. Hydroponic offers an alternative modern agriculture that has high potential in land and water use efficiency. However, this system still faces challenges in nutrient use efficiency (NU) as well as the stability of plant growth and yield. This study aims to examine the effect of Effective Microorganisms (EM) application on nutrient use efficiency, growth, and yield of Inthanon melon in the hydroponic system. The study used a Completely Randomized Design (CRD) method with 5 EM dose treatments (0, 150, 300, 450, and 600 ml/plant) and 5 replications. EM application was carried out by pouring it onto the growing medium/polybags according to the treatment dosage. Parameters observed included nutrient use efficiency, vegetative growth, and harvest yield. Based on the results, EM did not significantly affect the vegetative growth but rather affect generative growth, especially fruit weight in dose 450 ml/plant (P4). These results showed that EM can increase the yield of Inthanon melon variety.